2002
DOI: 10.1021/jp0140825
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Photochromism of 2-(2‘,4‘-Dinitrobenzyl)pyridine

Abstract: The photochromic behavior of 2-(2′,4′-dinitrobenzyl)pyridine (R-DNBP) has been followed in poly(methyl methacrylate) (PMMA) films and benzene solutions to clarify the behavior of a precursor state, previously identified in studies on crystalline R-DNBP at low temperatures. In PMMA films, photolysis at temperatures e50 K led to the concurrent formation of a NH tautomer and a colorless intermediate, which was stable for several hours. On irradiation at low temperatures and warming the sample, the colorless inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The proton transfer process from the methylene carbon atom towards the nitrogen atom of the pyridine has been characterized for a-DNBP [4][5][6], and assumed to be assisted by the o-nitro group. To test this assumption, it was synthesized the 2-(2' ,4' -diphenylsulfonylbenzyl)-pyridine [ 1 ], a new a-DNBP derivative in which the electron withdrawing nitro groups have been replaced by sulfone groups, and shown that this derivative is photochromic in solution and in the crystal.…”
Section: Discussionmentioning
confidence: 99%
“…The proton transfer process from the methylene carbon atom towards the nitrogen atom of the pyridine has been characterized for a-DNBP [4][5][6], and assumed to be assisted by the o-nitro group. To test this assumption, it was synthesized the 2-(2' ,4' -diphenylsulfonylbenzyl)-pyridine [ 1 ], a new a-DNBP derivative in which the electron withdrawing nitro groups have been replaced by sulfone groups, and shown that this derivative is photochromic in solution and in the crystal.…”
Section: Discussionmentioning
confidence: 99%
“…The final photoproduct from α-DNBP using light of λ = 370-420 nm is the NϪH quinoid tautomer (NϪH form), consistent with its IR, visible, and 2D NOESY 1 H NMR spectra (7) (Scheme I). The NϪH form arises from the short-lived aci-nitro tautomer (OϪH form), a tauto-merization that is supported by time dependent studies employing polarized reflection and absorption spectra combined with FT-IR and Raman spectral data obtained from a single crystal of irradiated α-DNBP (8) and from photolysis studies in poly(methylmethacrylate) films (9).…”
mentioning
confidence: 88%
“…[27] Since then, numerous pyridine-derived compounds have been explored for photo-responsive smart materials. [28,29] Recently, materials with both mechanochromic and photoresponsive properties have been reported, [30] which inspire us to further develop responding materials with integrated logic. In this paper, we successfully render sequential-stimuli induced stepwise-response by combining mechano-chromic and photoresponsive properties into single-component materials (Py-1-Py-3).…”
Section: Introductionmentioning
confidence: 99%
“…[ 27 ] Since then, numerous pyridine‐derived compounds have been explored for photo‐responsive smart materials. [ 28,29 ]…”
Section: Introductionmentioning
confidence: 99%